Analysis of Service Quality on Consumer Satisfaction at Indiegib Baby Shop, Baturaja, South Sumatra - Anita Mauliyanti; Syfa Harian Fajar Sapta; Hilwa Fitri Millenia (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
The development of digital technology has shifted the behavior of Indonesian consumers, especially the younger generation, towards using social media such as Instagram as the primary platform for online buying and selling transactions. This study aims to analyze the effect of service quality in online buying and selling on customer satisfaction at the Indiegib Baby Shop in Sukaraya, Baturaja, South Sumatra. A quantitative method was used, collecting data through a questionnaire from 286 store followers who made purchases. The analysis results show that the majority of respondents rated service quality and customer satisfaction as moderate, with aspects of responsiveness, communication, service speed, and clarity of shipping information still needing improvement. A chi-square statistical test revealed a significant effect of service quality on customer satisfaction. These findings are supported by interviews that emphasized the importance of response speed and information transparency in influencing loyalty. This study provides a practical contribution to MSMEs in optimizing online services as a key to sustainability and competitiveness in the increasingly competitive digital market.